2016
DOI: 10.15640/jeds.v4n1a3
|View full text |Cite
|
Sign up to set email alerts
|

Openness of the Economy, Diversification, Specialization, and Economic Growth

Abstract: This article examines whether openness of the economy promotes production diversification or production specialization and whether or not specialization/diversification spurs economic growth. International trade is important to stabilize and promote economic growth. However, promotion of international trade does not necessarily cause economic growth. This article focuses on the existence empirical patterns of production diversification/specialization between international trade and economic growth. The empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…This finding on diversification and economic growth is in line with Aamir (2018) that observes an insignificant-positive relationship between geographical export diversification and economic growth in Pakistan. Nworu (2017) noted that export diversification, particularly in the non-oil sectors, is vital to improving the revenue-based on the government while Kurihara & Fukushima (2016) observe that greater openness of the economy does not always mean the higher economic growth in emerging and developing countries. While Esu & Udonwa (2015) observe that economic diversification (proxied by non-oil trade), had a negative http://journal.uinjkt.ac.id/index.php/signifikan DOI: htttp://dx.doi.org/10.15408/sjie.v8i2.9861 impact on economic growth.…”
Section: Resultsmentioning
confidence: 99%
“…This finding on diversification and economic growth is in line with Aamir (2018) that observes an insignificant-positive relationship between geographical export diversification and economic growth in Pakistan. Nworu (2017) noted that export diversification, particularly in the non-oil sectors, is vital to improving the revenue-based on the government while Kurihara & Fukushima (2016) observe that greater openness of the economy does not always mean the higher economic growth in emerging and developing countries. While Esu & Udonwa (2015) observe that economic diversification (proxied by non-oil trade), had a negative http://journal.uinjkt.ac.id/index.php/signifikan DOI: htttp://dx.doi.org/10.15408/sjie.v8i2.9861 impact on economic growth.…”
Section: Resultsmentioning
confidence: 99%
“…Also, trade increases the export capacities via the imports of raw materials and capital goods that eventually lead economic growth. This finding is pertinent with Were (2015), Busse and Koeniger (2015), Pradhan et al (2017) and Keho (2017) but is not pertinent with Musila and Yiheyis (2015), Ali and Abdullah (2015), Kurihara and Fukushima (2016), and Moyo and Khobai (2018). Accordingly, labour and capital also provide their traditional role on fostering the economic growth.…”
Section: Pmg Estimation Resultsmentioning
confidence: 83%
“…For example, Were (2015); Busse and Koeniger (2015); Pradhan et al (2017) and Keho (2017) found positive and significant impact of trade on economic growth. In contrast, Musila and Yiheyis (2015), Ali and Abdullah (2015), Kurihara and Fukushima (2016), and Moyo and Khobai (2018) found an inverse or limited support on this relationship. The studies undertaken by Were (2015), Busse and Koeniger (2015) and Pradhan et al (2017) were conducted on a sample of 85 countries, 108 countries, and the ASEAN countries, respectively.…”
Section: Economic Growth-trade Nexusmentioning
confidence: 94%
See 1 more Smart Citation
“…At the international level, Kurihara and Fukushima (2016) examined the impact of economic development on the relationship between growth and export diversification. Additionally, the role of trade openness in stimulating export diversification or concentration (specialization) was examined, and whether this contributed to economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%